Morphological features of adenohypophysis stillborn from HIV-infected mothers - Sherstiuk S.A.; Sorokina I.V. (Морфологія, 2012)
Adenohypophysis stillborn from HIV-infected mothers had a high functional stress for long periods of fetal devel-opment, leading to inhibition of its functional state, as evidenced by the decrease in the diameter of cells, reducing their se-cretory granules, and increased nuclear-cytoplasmic index. In the antenatal period of development in the adenohypophysis of stillbirths from HIV-infected mothers apparently failed embryo genesis, which appeared violation of a population growth of acidophilic cells. Inhibition of functional activ ity of the entire population of cells of the adenohypophysis indicate a failure of compensatory possibilities of the body, which in future may be the cause of severe endocrinopathies.